People with disabilities and the labor market – Literature review (Research, Society and Development, 2022)
We understand people with disabilities as those who have long-term impairments of a physical, mental, intellectual or sensory nature, or who, in interaction with various social barriers, can have their full and effective participation in the impaired or impeded society. The objective of this study was to analyze the literature on the experience of people with disabilities (PwD) in the labor market. It is an integrative review of the literature, where we analyze, through the Content Analysis procedure, 28 articles collected in the Portal Periódicos Capes. The given possibilities to build five categories: 1) Guarantee of direct access to the labor market; 2) Recruitment of people with disabilities; 3) Barriers to access and permanence in the job market; 4) Development of the disabled worker; 5) Breaking down the barriers, which argue that there is still a long way to go for the effective inclusion of PwD in the labor market, so that what happens is a compulsory hiring so that the organizations do not suffer sanctions from the Public Ministry. It has also been observed that many organizations sell the perception of being inclusive and hardly use the image of PwD to gain visibility. Finally, the true inclusion requires the transformation of two work spaces into spaces of social justice and care, fleeing from the perspective of “redequation” of the physical space for inclusion and finding the valorization of the power of diversity.